Ubiquitin-dependent trafficking and turnover of ionotropic glutamate receptors - Goo, Marisa S.; Scudder, Samantha L.; Patrick, Gentry N. (Frontiers in Molecular Neuroscience, 2015)
Changes in synaptic strength underlie the basis of learning and memory and are controlled, in part, by the insertion or removal of AMPA-type glutamate receptors at the postsynaptic membrane of excitatory synapses. Once internalized, these receptors may be recycled back to the plasma membrane by subunit-specific interactions with other proteins or by post-translational modifications such as phosphorylation. Alternatively, these receptors may be targeted for destruction by multiple degradation pathways in the cell. Ubiquitination, another post-translational modification, has recently emerged as a key signal that regulates the recycling and trafficking of glutamate receptors. In this review, we will discuss recent findings on the role of ubiquitination in the trafficking and turnover of ionotropic glutamate receptors and plasticity of excitatory synapses.